Use of Antiplatelet Agents Is Inversely Associated With Liver Fibrosis in Patients With Cardiovascular Disease. Issue 12 (5th October 2018) - Schwarzkopf, Katharina; Bojunga, Joerg; Rüschenbaum, Sabrina; Martinez, Yolanda; Mücke, Marcus M.; Seeger, Florian; Schoelzel, Fabian; Zeuzem, Stefan; Friedrich‐Rust, Mireen; Lange, Christian M.
Abstract : Platelets participate in the development of liver fibrosis in animal models, but little is known about the benefit of antiplatelet agents in preventing liver fibrosis in humans. We therefore explored the relationship between the use of antiplatelet agents and liver fibrosis in a prospective cohort study of patients at high risk of liver fibrosis and cardiovascular events. Consecutive patients undergoing elective coronary angiography at the University Hospital Frankfurt were prospectively included in the present study. Associations between use of antiplatelet agents (acetyl salicylic acid, P2Y12 receptor antagonists) and liver fibrosis were assessed in regression models, and the relationship between platelet‐derived growth factor beta (PDGF‐β) serum concentration, platelets, liver fibrosis, and use of antiplatelet agents was characterized. Out of 505 included patients, 337 (67%) received antiplatelet agents and 134 (27%) had liver fibrosis defined as a FibroScan transient elastography (TE) value ≥7.9 kPa. Use of antiplatelet agents was inversely associated with the presence of liver fibrosis in univariate and multivariate analyses (multivariate odds ratio [OR], 0.67; 95% confidence interval [CI], 0.51‐0.89; P = 0.006). Use of antiplatelet agents was also inversely associated with FibroTest values (beta, –0.38; SD beta, 0.15; P = 0.02). Furthermore, there was a significant correlation between platelet counts and PDGF‐β serum concentration (rho, 0.33; P < 0.0001), but PDGF‐β serum levels were not affected by antiplatelet agents. Conclusion : There is a protective association between the use of antiplatelet agents and occurrence of liver fibrosis. A randomized controlled trial is needed to explore causality and the potential of antiplatelet agents as antifibrotic therapy in patients at risk for liver fibrosis progression.